2010
DOI: 10.1128/jcm.01130-09
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Oligonucleotide Chip Based on the 16S-23S rRNA Gene Spacer Region for Detection of Pathogenic Microorganisms Associated with Sepsis

Abstract: Oligonucleotide chips targeting the bacterial internal transcribed spacer region (ITS) of the 16S-23S rRNA gene, which contains genus-and species-specific regions, were developed and evaluated. Forty-three sequences were designed consisting of 1 universal, 3 Gram stain-specific, 9 genus-specific, and 30 species-specific probes. The specificity of the probes was confirmed using bacterial type strains including 54 of 52 species belonging to 18 genera. The performance of the probes was evaluated using 825 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Various target regions are used to identify pathogens in oligonucleotide microarray methods. These regions include 16S rDNA, 23S rDNA and 16S-23S rDNA internal transcribed spacer region (ITS) (14,16,26,27). The 23S rDNA genes appear to be the best performing regions as target sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Various target regions are used to identify pathogens in oligonucleotide microarray methods. These regions include 16S rDNA, 23S rDNA and 16S-23S rDNA internal transcribed spacer region (ITS) (14,16,26,27). The 23S rDNA genes appear to be the best performing regions as target sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Mori et al (2004) suggested that phylogenetic analysis based on tripeptidase (PepT) and dipeptidase (PepV) genes may aid in a more precise index of classification of L. lactis subspecies. Beside 16S rRNA gene, 16S-23S rRNA gene intergenic spacer region or 23S rRNA gene have also been used to identify bacterial species (Blaiotta et al 2002;Mohania et al 2008;Kim et al 2010). However, there are no satisfactory databases for these genes for the development of L. lactis identification methods, except for 16S rRNA gene.…”
Section: Discussionmentioning
confidence: 99%
“…A DNA microarray for the detection 30 bacteria associated with sepsis contained 1 universal, 3 Gram stain-specific, 9 genus-specific, and 30 species-specific probes directed against the 16S-23S rRNA ITS region. The microarray was validated with 825 positive blood culture samples from which 708 (85.8%) were identified correctly by the oligonucleotide chip [27]. Negoro et al [30] developed a DNA microarray which covered 72 bacteria which are often identified in positive blood cultures in combination with a PCR using universal PCR primers to amplify a variable region of the 16S rDNA.…”
Section: Blood Stream Infections/sepsismentioning
confidence: 99%